Chronic pain, a narrative review for the internist in 2024 - Sovaila Silvia; Purcarea Adrian; Neculau Andrea (Sciendo, 2024)
Chronic pain is a complex and pervasive condition that profoundly affects individuals physically, emotionally, and socially. This narrative review aims to provide internists and healthcare professionals with a comprehensive overview of chronic pain, its various types, pathophysiology, epidemiology, clinical presentation, evaluation tools, and the burden it imposes on patients. We discuss the importance of recognizing chronic pain as a legitimate condition and the need for a compassionate, individualized approach to management. The review highlights the role of both pharmacological and non-pharmacological interventions in treating chronic pain, emphasizing the value of reducing pain, improving function, enhancing quality of life, and minimizing medication dependence. Additionally, we touch upon the promising future of pain treatment, including advancements in technology and personalized medicine. While not a comprehensive systematic review, this article serves as a valuable resource for healthcare providers seeking to understand, manage, and treat chronic pain effectively in their daily practice.